UPAYA MENINGKATKAN KUNJUNGAN WISATAWAN KE SENTRA INDUSTRI BATIK DI LENDAH KULON PROGO YOGYAKARTA - Damiasih, Damiasih; Kusdarwati, Hasna (Kepariwisataan: Jurnal Ilmiah, 2016)
Lendah Batik Industry Center Kulon Progo is an area located in the Industrial Center Lendah District of Kulon Progo Regency in the region where there are range between 10 – 18 Batik Craftsmen Group and more than 50 batik batik consisting of fixed and home . In this area there are a variety of motives in each production site .The results show that efforts to do in increasing the number of tourists visiting Batik Industry Center at Lendah Kulon Progo is to continue to promote the production through the exhibition by distributing business cards and brochures , promotion through social media such as fuel and the Internet . Participation provided by the public such as batik Batik Industry Center region such as batik previous work has had more than 30 years as a batik in the city of Yogyakarta . Constraints faced by the group of craftsmen Batik as geographical location far from the city center . Accessibility is slightly delayed due to impassable roads is a main road for trucs of sand miners . Then the lack of insight Craftsmen Batik Group in operating accounts only a few social media accounts batik craftsmen group that uses the media. Keywords: Batik, Industry, Tourist, Visitor, Craftsmen